PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERINTEGRASI CULTURALLY RESPONSIVE TEACHING (CRT) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS X IPA 2 SMA NEGERI 7 MATARAM PADA MATA PELAJARAN KIMIA TAHUN AJARAN 2022/2023 - Anjalika Sari; Yunita Arian Sari; Dina Namira (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2023)
This study is a Classroom Action Research that aims to investigate whether the implementation of the Problem-Based Learning model integrated with Culturally Responsive Teaching (CRT) can enhance the motivation and learning outcomes of X IPA 2 at SMA Negeri 7 Mataram in the subject of Chemistry for the academic year 2022/2023. The research employs the Classroom Action Research method, consisting of planning, acting, observing, and reflecting. Data sources include both quantitative and qualitative data, encompassing pre-test and post-test results, observations of the teaching and learning process, questionnaire responses, daily journals/field notes, and activity photos. The research is conducted collaboratively with fellow teachers to assess student motivation and learning outcomes after implementing the intervention in two cycles, with each cycle comprising two sessions. The results of the study indicate that the application of the Problem-Based Learning model integrated with Culturally Responsive Teaching demonstrates high student motivation, with an agreement percentage of 89%. Additionally, there is an evident improvement in student engagement, as shown by an average class activity percentage of 60.96% in the first cycle and 87% in the second cycle. Furthermore, there is an enhancement in student learning outcomes, with a proficiency percentage increasing from 77% in the first cycle to 86% in the second cycle.